The processing of facial identity and expression is interactive, but dependent on task and experience - Yankouskaya, Alla; Humphreys, Glyn W.; Rotshtein, Pia (Frontiers in Human Neuroscience, 2014)
Facial identity and emotional expressions are two important sources of information for daily social interaction. However the link between these two aspects of face processing has been the focus of debate for the past 2 decades. Three polar views have been advocated: (1) there is separate and parallel processing of identity and emotional expression signals derived from faces; (2) there is asymmetric processing with the computation of emotion in faces depending on facial identity coding but not vice versa; and (3) there is integrated processing of facial identity and emotion. Here we present studies primarily using methods from mathematical psychology that formally provide a direct test of the relations between the processing of facial identity and emotion. We focus on the ‘Garner’ paradigm, the composite face effect and divided attention task. We further ask whether the architecture of face-related processes is fixed or flexible and whether it can be shaped by experience. We conclude that formal methods of testing the relations between processes show that the processing of facial identity and expressions interact, and hence are not fully independent. We further demonstrate that the architecture of the relations depends on experience; where experience leads to higher degree of inter-dependence in the processing of identity and expressions.